2005
DOI: 10.1111/j.1526-100x.2005.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Fire to Long‐Unburned Pinus palustris Ecosystems: Novel Fire Effects and Consequences for Long‐Unburned Ecosystems

Abstract: Biologically rich savannas and woodlands dominated by Pinus palustris once dominated the southeastern U.S. landscape. With European settlement, fire suppression, and landscape fragmentation, this ecosystem has been reduced in area by 97%. Half of remnant forests are not burned with sufficient frequency, leading to declines in plant and animal species richness. For these fire-suppressed ecosystems a major regional conservation goal has been ecological restoration, primarily through the reinitiation of historic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 50 publications
2
161
0
Order By: Relevance
“…In the experimental plots, C and N concentrations were higher near the trunk where litter accumulation and forest floor depth are generally greater [19,51,52]. Indeed, Varner et al [22] reported that without fire, litter from pines and hardwoods could accumulate as deep as 25 cm near the trunk of large trees. Burning of accumulated organic materials results in losses of C and N via volatilization, but also as an input, through ash, of soil C and N via leaching into the mineral soil [53].…”
Section: Soil Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experimental plots, C and N concentrations were higher near the trunk where litter accumulation and forest floor depth are generally greater [19,51,52]. Indeed, Varner et al [22] reported that without fire, litter from pines and hardwoods could accumulate as deep as 25 cm near the trunk of large trees. Burning of accumulated organic materials results in losses of C and N via volatilization, but also as an input, through ash, of soil C and N via leaching into the mineral soil [53].…”
Section: Soil Gradientmentioning
confidence: 99%
“…Modern fire suppression from forest management or agriculture, however, has led to hardwood encroachment, the development of a woody mid-story [25] and altered cover and composition of understory vegetation [23,[26][27][28]. Without fire, litter from pines and hardwoods can accumulate as deep as 25 cm, especially near the bases of large trees [22]. In savanna-type forests, levels of soil organic matter and nutrients are generally higher below the tree canopy [4,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a point transect count census technique, adapted for the open habitat at Eglin, to record the relative abundance of cavity-nesting birds within each plot between 8 April and 21 June of 2002-2005(Provencher et al 2002. Each year, we conducted two rounds of censusing on two plots per morning within three hours after sunrise (totaling 24 census stations).…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…Researchers have found that bark thicker than 12 mm will protect the stem cambium of most pines during prescribed fires (Fahnestock and Hare 1964). Even though pine bark is a good insulator, cambial damage can occur if the fire duration is long, which typically occurs if fuels (e.g., sloughed bark and needles) have accumulated at the base of a tree (Menges and Deyrup 2001;Varner et al 2005). Damage to either the crown or cambium often results in death of trees months later.…”
Section: Abiotic Disturbance Effects Under Future Climatementioning
confidence: 99%